An algorithm to isolate poles in Feynman diagrams preserving background gauge invariance and supersymmetry - Abdalla, E.; Abdalla, M. C.B. (Elsevier, 1986)
We regularize the heat-kernel expansion of propagators in the presence of background fields. This leads to a renormalized perturbation series which is gauge-invariant and supersymmetric with respect to background variations. This procedure permits isolation of singularities in the computation of the effective action, obeying the above symmetries. © 1986.